Kualitas Pelayanan Akademik Terhadap Citra Perguruan Tinggi - Riska Tyas Prahesti; Poppy Ruliana; Kinkin Yuliati Subarsa (Jayapangus Press, 2021)
Service quality for a service company is very important to frame or create an image in the eyes of its consumers. The Inter-Study College of Communication is one of the private universities that is expected to be able to produce graduates who are competitive, competent, by creating professional human resources. Academic service is the vanguard for an institution that determines the success or failure of an institution in creating and maintaining its image, either a positive image or a negative image. The expectations of students for the quality of academic services will vary greatly even though the quality of academic services is the same, while the image of the institution cannot be formed in a short time, a good image must also be maintained by providing good service quality, and this is the basis of this research. conducted to test the effect of the quality of academic services on the image of the STIKOM Inter Study. In research, service quality has several variables, namely reliability, responsiveness, empathy, assurance and tangible. This research is an explanative study using a quantitative approach and positivism paradigm. The population in this study were students of STIKOM InterStudi. The data collection technique is done by using non probability sampling. Based on the calculation of the sample formula, it is known that the number of samples in this study were 95 students. The results of the research on academic service quality show that the variables namely reliability, responsiveness, empathy, assurance and tangible have a significant positive effect on image.